Treatment of varicose ulcer of the lower limbs by surgery and Unna boot: savings for the Brazilian healthcare system - Belczak,Sergio Quilici (2011)
ABSTRACT Objective: To perform an analysis of the costs of treatment of varicose ulcers by radical surgery of varices and the use of Unna boot. Methods: Fifteen outpatients were selected to receive treatment of varicose ulcers with radical surgery and Unna boot. The total cost of treatment was calculated (hospitalization, surgery, dressings, and outpatient's follow-up visits) and compared to the cost of clinical follow-up with daily simple dressing changes. Results: The proposed treatment was on average 55.71% more economical than the management with daily dressings (approximately US$452.32 versus US$1,021.39). Conclusion: Radical varicose vein surgery associated with the use of the Unna boot proved meaningly less expensive for the public health system than clinical follow-up with daily dressings.